PELAYANAN KESEHATAN GRATIS LANSIA DAN EDUKASI UNTUK MENCIPTAKAN MASYARAKAT YANG PEKA TERHADAP KESEHATAN DI DESA KARYA UTAMA KECAMATAN CIKEDAL KABUPATEN PANDEGLANG - Nuraini, Intan; Sulaeman, Yeni; Nugraha, Rifki Arif; Zannah, Rihatul (STAI Darul Qalam Tangerang, 2024)
Elderly age is the final stage of development in the human life cycle and is marked by the physical development of a person and his physiological stress condition. The elderly are also related to a decrease in ability, sensitivity and individual life. According to ratnawati in Widyawati & Sari (2020) is a person who has reached the age of 60 years or more, he is unable to earn his own living to meet the needs of life and is marked by a decrease in the body to adapt. By holding this socialis, the people in Karya Utama village are more aware of their health. The most important program is to open free health check services for the elderly in Karya Utama Village. . With a target age of 60 years to the older age, the community, especially the elderly, is not aware of the importance of health in the elderly, a strategy with an approach or door to door to every elderly home in the main work village and few questions are asked. Community service activities are carried out in order to increase knowledge, understanding and community participation in maintaining health. Based on the results of the preliminary study, it shows that in Kp. Cirumput Karya Utama Village there are 59 elderly people overall, ranging in age from 60 years to 75 years and above. The method used is through home visits by conducting community approaches, observations, interviews, socialization and mentoring. The results obtained were information on elderly respondents based on age, occupation, respondents, and gender. Observation activities obtained information about the health condition of the elderly, both physical and non-physical. The knot can increase the understanding for the elderly about the definition, causes, symptoms, risks, activities, and understanding of the importance of consuming healthy food